The Extent of The Use of Performance-Based Evaluation in Distance Education Among Secondary School Mathematics Teachers - Al-Shanqiti, Abdullah Mohammed Mahmoud; Al-Balawi, Salem Abdulrahman (Journal of Curriculum and Teaching Methodology, 2022)
The present study aimed to identify the extent of the use of performance-based evaluation in distance education among secondary school mathematics teachers، in both aspects (planning، implementation، feedback) and the study consists of all mathematics teachers for the secondary stage in Medina for the academic year، while the study sample consisted of (123) teachers. Whereas the study tool was the questionnaire that consisted of (32) items divided into three axes: the planning axis، and it consisted of (11) paragraphs and the focus of implementation، and it consisted of (10) paragraphs and the focus of feedback، and it consisted of (11) paragraphs.The results of the study showed that the "implementation" axis was the most used for performance-based evaluation in distance education for mathematics teachers in the secondary stage, where the arithmetic mean of the implementation axis reached (4.01), with a relative weight of (80.20). While the "Planning" axis came in second place with an average of (3.96), with a relative weight of (79.20).While the "Feedback" axis came in third place with a mean of (3.76),with a relative weight of (75.20), The study recommended a number of recommendations, the most important of which are: Issuing guides explaining to the teacher and learner the method and steps for using the performance-based evaluation strategy and providing and developing programs and media in mathematics education in line with the use of the performance-based evaluation strategy in distance education
Keywords: Performance-based assessment; Distance education; Secondary school; Mathematics education